Emission and in-cylinder combustion characteristics of a spark ignition engine operated on binary mixtures of gas and liquid fuels - Gonca, Guven; Hocaoglu, Mehmet Fatih (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
In this study, three different gas fuels such as hydrogen, propane, methane and six different liquid fuels such as, benzene, gasoline, toluene, hexane, methanol and ethanol have been combined and combustion characteristics have been simulated for a spark ignition engine (SIE). Variation of in-cylinder temperature, in-cylinder pressure, CO, CO2 and NO has been investigated. The gas fuel ratios in the mixtures were changed between 0 and 100% by mass. It was investigated that how the addition of gaseous fuels to liquid fuels at different ratios affects the combustion characteristics and emission formation. The gas fuel ratios considerably affected emission and combustion specifications of the engine. Increasing liquefied gas fuel ratio in the mixture leads to decrement in the temperature of charge. The maximum pressure first increases with increasing gas fuel ratio and then start to minimize after maximum pressure. The maximum peak pressure values are observed at 50% gasoline and 50% methane, 75% gasoline and 25% propane, 50% gasoline-50% hydrogen as 48.1 bar, 46 bar and 62.4 bar for different gas fuel mixtures. The minimum peak pressure value is displayed at 100% methanol as 44.06 bar. The maximum temperature value is observed at 100% benzene as 2582 K and its minimum value seems at 100% hydrogen as 2059 K. The maximum mass fractions of CO, CO2, NO are observed at 100% benzene as 0.0271, 0.161, 0.0076, the minimum mass fraction of CO2 is observed at 100% methane as 0.095. The minimum mass fraction of CO is observed at 100% methanol as 0.01243. The minimum mass fraction of NO is observed at 100% hydrogen as 0.00085. The fuels are ranked using a multicriteria decision-making algorithm called AHP after evaluating the values of all performance criteria and their respective sub-criteria, including in-cylinder pressure, in-cylinder temperature, NO, CO2 and CO to get preference rank between fuels.(c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hidrogen; Methane; Propane; Liquid and gas fuels; Spark ignition engine; Multi criteria decision making; DIRECT-INJECTION ENGINE; SAUDI-ARABIAN RON91; N-HEXANE; HYDROGEN ADDITION; EXHAUST EMISSIONS; GASOLINE BLENDS; PERFORMANCE; BENZENE; ETHANOL; OPTIMIZATION; Chemistry; Electrochemistry; Energy & Fuels